Open source software appropriation in Malaysian public sector - Ab. Rahim, Nor Zairah; Alias, Rose Alinda (2006)
Many models and frameworks have been developed from IS studies in investigating the penetration, implementation and adoption of specific technologies in organizations. However, many of these models have not focused or considered in depth the later stages, after the initial introduction of the technology. This study tries to fill this gap by examining the technology appropriation theory, which is related to how organizations adopt technology and use them after the technology has been initial introduced in order to achieve organizational benefits. The focus is on the Open Source Software (OSS) in Malaysian Public Sector with relation to the establishment of Open Source Competency Centre by MAMPU in 2001. The study will look at to what extend have the organizations in the Malaysian public sector appropriated the OSS from multiple perspectives. Case study will be conducted to the chosen organizations to gather the empirical data for this study.